Grain size constraints on arsenic concentration in shallow wells of Nawalparasi, Nepal - Shrestha, Suresh Das; Brikowski, Tom; Smith, Linda; Shei, Tai-Chyi (Journal of Nepal Geological Society, 2004)
Occurrence of arsenic in shallow aquifers was studied from the Nawalparasi district in west Nepal. A higher concentration of arsenic was found in the wells from the north as compared to those from the south. The arsenic level in the north reaches a maximum of 694ppb as compared to a value of 27 ppb in the south near the Nepal-India border. The arsenic concentration analyses carried out in selected sites from March to September 2003 indicate a large variation (exceeding 200%) in the north as compared to the central and southern regions. A general increase in grain size from north to south was observed in the well logs. Generally, fine sediments like clay and silt constitute more than 80% of the drilled depth in the north (i.e., at Panchnagar), while the fines are about 32% in the south (i.e., at Bhujawa). This type of grain size distribution is in contrast to the generally observed fining-southwards pattern in the Terai.